The Effects of Inorganic Phosphorus Levels on Phosphorus Utilization, Local Bone-Derived Regulators, and BMP/MAPK Pathway in Primary Cultured Osteoblasts of Broiler Chicks - Li, Tingting; Cao, Sumei; Liao, Xiudong; Shao, Yuxin; Zhang, Liyang; Lu, Lin; Liu, Zongping; Luo, Xugang (Frontiers in Veterinary Science, 2022)
Understanding the underlying mechanisms that regulate the bone phosphorus (P) utilization would be helpful for developing feasible strategies to improve utilization efficiency of P in poultry. We aimed to investigate the effects of inorganic P levels on P utilization, local bone-derived regulators and bone morphogenetic protein/mitogen-activated protein kinase (BMP/MAPK) pathway in primary cultured osteoblasts of broiler chicks in order to address whether local bone-derived regulators or BMP/MAPK pathway was involved in regulating the bone P utilization of broilers using an in vitro model. The primary cultured tibial osteoblasts of broiler chicks were randomly divided into one of five treatments with six replicates for each treatment. Then, cells were respectively incubated with 0.0, 0.5, 1.0, 1.5, or 2.0 mmol/L of added P as NaH2PO4 for 24 days. The results showed that as added P levels increased, tibial osteoblastic P retention rate, number and area of mineralized nodules, the mRNA expressions of endopeptidases on the X chromosome (PHEX), dentin matrix protein 1 (DMP1), bone morphogenetic protein 2 (BMP2), and the mRNA and protein expressions of matrix extracellular phosphoglycoprotein (MEPE) increased linearly (p < 0.001) or quadratically (p < 0.04), while extracellular signal-regulated kinase 1 (ERK1) mRNA expression and c-Jun N-terminal kinase 1 (JNK1) phosphorylated level decreased linearly (p < 0.02) or quadratically (p < 0.01). Correlation analyses showed that tibial osteoblastic P retention rate was positively correlated (r = 0.452–0.564, p < 0.03) with MEPE and BMP2 mRNA expressions. Furthermore, both number and area of mineralized nodules were positively correlated (r = 0.414–0.612, p < 0.03) with PHEX, DMP1, MEPE, and BMP2 mRNA expressions but negatively correlated (r = −0.566 to −0.414, p < 0.04) with the ERK1 mRNA expression and JNK1 phosphorylated level. These results suggested that P utilization in primary cultured tibial osteoblasts of broiler chicks might be partly regulated by PHEX, DMP1, MEPE, BMP2, ERK1, and JNK1.